Stereotypes of Cendrawasih Mess Residents toward Papuan People (Oratio Directa, 2024)
Stereotyping is a process of social classification in which a group simplifies or generalizes signs about another group, explicitly or implicitly presenting judgments or assumptions about behavior, characteristics, or history. Social interaction at Mess Cendrawasih involves diverse Javanese, Batak, Palembang, and Papuan cultural backgrounds and may produce intercultural communication barriers. This study uses the uncertainty reduction theory of Charles Berger and Richard Calabrese and a qualitative approach with interviews. The findings identify positive stereotypes in helpful and polite behavior, and negative stereotypes in perceptions of high temperament, alcohol consumption, and gambling. These stereotypes do not occur on a scale that causes discrimination or disrupts harmony among the residents' diverse cultures.
Keywords: Stereotypes; Uncertainty reduction theory; Intercultural communication; Papuan people; Cultural harmony